تحليل استراتيجية خطابات رئيس الجمهورية خلال نهاية العهدة الثالثة - ريغي أسماء (My University, 2017)
Our study, which deals with " the strategy of speeches of the President of the republic Abdel Aziz Bouteflika during the end of the third mandate ", aims at knowing the borders through which the president speeches are presented and focusing on the implications that they have carried to try to know the power of authority and the impact of the political speech on the life of the Algerian political society. And we have started from the principal question which is: what are the mechanics of the political présidencial speech of ABDEL AZIZ BOUTEFLIKA ?and what is its role in the political life in Alegeria ? and how did the prisident ABDEL AZIZ BOUTEFLIKA induce the Alegerian people through his political speeches since 2012 ? This problematic led us to ask the following some suk-questions: - What is intended by the analysis of the political speech ? And how can we distinguish between the political speech and the other speeches in the society ? - What are the issues and the ideas that have been dealt with in the political content of the speech ? - What is generally meant by the strategy ? and what is its definition in the political speech ? To answer these questions, we adopted, in our study, a reseach strategy that included an introduction, three chapters and a conclusion. The former dealt whith the layout of the political speech, the second with the strategies of the political speech in the Algerian presidential speech, while in its experimental chapter, we dealt with analysis of written speeches, audio-visial and written letters. In our analysis, we adopted two approaches of study : the ethnographic communicative approach and the semiological approach and this is from a delibrite sample that limits the period of time of the determined work. This study came out with a set of the following most important results : - The speaker should adopt a political effective contact as a means of interaction of the political behaviour between the political formations and the authority to pass the messages and the programmes issued by the ruling political system. - The political speech aims basically at legimizing the actions of the political authority in the past, the present and the future and this is what we can touch through the arguments and evidences that have been employed by the sender by recalling the sufferings of the Algerian people during the colonial era and what must be done as achievements and developed projects in the present to secure the future of the next generation. - The political issues that the Algerian political speek seeks to treat and achieve at the real level are represented in investment and development projects, a great participation in the elections, taking care of the youth and the promotion of the woman rights. - Through the analysis, we can see that the presidential speek is mostly polished and sometimes on a bit of complexity in drafting and it can seem that is has been though of and prepared before.whille its used language is caracterazed by simplicity and the direct spontaneity in diction and even the sender can get out of the written text. - The political presidential speek carries various expressive images, and fresh words based on popular sayings to support arguments and evidences and they can be taken from the Islamic Sharia. - Employment of the President more than a strategy to build a political speech, corporate strategy, strategic guidelines and strategic and persuasive whole in order to attain and achieve his goal than.
Keywords: The speek strategy, the political speek, the solidarity strategy, the guiding strategy, the persuasive strategy.